Ayat-ayat Perdamaian: Dekonstruksi Tafsir ala Jane Dammen McAuliffe - Fadhli Lukman (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Its is the matter of fact that Muslims way to behave, including to behave  before other communities, such as Christians, comes from the Qur’an. To understand how Muslims do something on their religiousity is then to come analyzing the Qur’an. This is what Jane Dammen McAulife fully aware of; She is curious of how the Qur’an presents the Christians. However, since the Qur’an further controlled by exegesis, it become an integral aspect in her way to study Qura’nic Christians. This paper will descriptively explore Jane Dammen McAuliffe’s though on Qur’anic presentation to Christians. Her dissertation will be the basis of analysis. However, we previously present the mapping of her whole thought to gain the comprehensive understanding on her complete thought. In context of Qur’anic Christians, she concludes that since the exegesis controls the Qur’an, Qur’anic Christians refer to nor historical Christians nor the living community call themselves as Christians.